Healthier Lipid Profiles of Japanese Adults, Especially in Women with Elevated High-Density Lipoprotein Cholesterol (HDL-C), Are Associated with Low HDL-C Peroxide Content - Loni Berkowitz-Fiebich; Shelby M. Flaherty; Shinobu Kitayama; Mayumi Karasawa; Norito Kawakami; Attilio Rigotti; Christopher L. Coe (Antioxidants)
Japanese adults typically have healthier lipid profiles than American and European adults and a lower prevalence and later onset of atherosclerotic cardiovascular disease (ASCVD). Many Japanese also have uniquely elevated levels of high-density lipoprotein cholesterol (HDL-C). The following analysis examined the relationship between HDL-C level and HDL-C peroxide content, a bioindicator of unhealthy lipid metabolism in Japanese adults. Blood samples were collected from 463 participants, 31–84 years of age, who lived in Tokyo. A second blood sample was collected 5 years later from 241 of the participants, allowing us to evaluate the temporal stability of the inverse correlation between HDL-C level and HDL-C peroxide content. Glucoregulation and inflammatory activity were assessed because both can be associated with dyslipidemia and HDL-C dysfunction. Obesity and central adiposity were also considered. Overall, women had healthier HDL-C profiles than men. Elevated HDL-C (>90 mg/dL) was common (16.6%) and found more often in women. Higher HDL-C peroxide content was associated with older age and central adiposity and incremented further when HA1c and CRP were higher. When assessed 5 years later, lower HDL-C peroxide content continued to be evident in adults with higher HDL-C. While similar associations have been described for other populations, most Japanese adults typically had healthier levels of HDL-C with lower HDL-C peroxide content than previously reported for American adults.